Protonation status and control mechanism of flavin–oxygen intermediates in the reaction of bacterial luciferase - Tinikul, Ruchanok; Lawan, Narin; Akeratchatapan, Nattanon; Pimviriyakul, Panu; Chinantuya, Wachirawit; Suadee, Chutintorn; Sucharitakul, Jeerus; Chenprakhon, Pirom; Ballou, David P.; Entsch, Barrie; Chaiyen, Pimchai (The FEBS journal, 2021)
Bacterial luciferase proceeds bioluminescent reaction by generating a reactive intermediate of flavin C4a‐oxygen adduct. The intermediate is first generated in a protonated form of flavin C4a‐hydroperoxide, which is unable to react with an aldehyde. The active site His44 functions as an essential proton or to convert the flavin C4a‐hydroperoxide to a bioluminescent active flavin C4a‐peroxide. Bacterial luciferase catalyzes a bioluminescent reaction by oxidizing long‐chain aldehydes to acids using reduced FMN and oxygen as co‐substrates. Although a flavin C4a‐peroxide anion is postulated to be the intermediate reacting with aldehyde prior to light liberation, no clear identification of the protonation status of this intermediate has been reported. Here, transient kinetics, pH variation, and site‐directed mutagenesis were employed to probe the protonation state of the flavin C4a‐hydroperoxide in bacterial luciferase. The first observed intermediate, with a λmax of 385 nm, transformed to an intermediate with a λmax of 375 nm. Spectra of the first observed intermediate were pH‐dependent, with a λmax of 385 nm at pH < 8.5 and 375 at pH > 9, correlating with a pKa of 7.7–8.1. These data are consistent with the first observed flavin C4a intermediate at pH < 8.5 being the protonated flavin C4a‐hydroperoxide, which loses a proton to become an active flavin C4a‐peroxide. Stopped‐flow studies of His44Ala, His44Asp, and His44Asn variants showed only a single intermediate with a λmax of 385 nm at all pH values, and none of these variants generate light. These data indicate that His44 variants only form a flavin C4a‐hydroperoxide, but not an active flavin C4a‐peroxide, indicating an essential role for His44 in deprotonating the flavin C4a‐hydroperoxide and initiating chemical catalysis. We also investigated the function of the adjacent His45; stopped‐flow data and molecular dynamics simulations identify the role of this residue in binding reduced FMN.